Colombia Turning the Tide : Water Security for Recovery and Sustainable Growth - World Bank (World Bank, Washington, DC, 2020)
Many water bodies are contaminated, affecting public health, increasing the costs to treating water for drinking purpose, and reducing potential use for other sectors such as agriculture. There is a wide variation in efficiency depending on the sector; with proper management of water and measures to increase resilience, the productivity of water in Colombia can improve substantially. Taken together, these conditions are clear warning signs of water insecurity - and the country should move quickly to address them. This policy brief contains three sections that summarize the challenges, the key messages, and the policy recommendations. The report contains the full extent of the water security diagnostic study, which involved a participatory and consultations with various stakeholders from the Government of Colombia, academic institutions, and civil society organizations. It offers a summary of evidence and information of the key critical focus areas of the report; and contains sources, methods, references, and data to guide the reader on the main findings. The policy brief is intended for policy makers and broader audiences around five strategic themes: water and territorial development, water and human capital, water and resilience, water and ecosystems, and water and the circular economy.